Implementation of Lean management Practices in Azerbaijan (on the Example of a Private Company) - Alaskarova, Yelena; Aleskerova, Alina; Dr. Daróczi, Miklós (International Journal of Engineering and Management Sciences, 2023)
Organizations are facing crucial modifications as global market and conditions change day after day. To keep up with fast changing realities, it’s important to apply innovation decisions to the current stage of organizations. Lean management consolidates tools and techniques to revert from traditional way of operating to the new human oriented one. In the carried-out research its outlined, human resources management plays a big role in spreading and supporting lean initiatives. It was suggested that, Lean and Human resources management are compatible and should work together to obtain sustainable success by implementation of an innovation approach such as Lean. Both lean management and human resource management focus on the same goals with different methods in terms of control of businesses. All positivist approaches and practices are included in these approaches and practices, which are developed with a focus on the interests of the community, in order for the process to be concluded positively. The employee-centred management approach of human resources management is crucial to lead and maintain good environment in the teams. For this reason, in the lean management philosophy, it is aware that the corporate structure has responsibilities in terms of training the employees, eliminating their problems and supporting them in struggling with the responsibilities they undertake. This paper is quantitative, online survey has been conducted with employees of a private company in Azerbaijan and results were analysed in statistical analysis software SPSS and relevant suggestions and recommendation were given for reorganization to enable lean friendly environment on a sample of the given company.